Bleeding after extraction tooth: case series: Perdarahan pasca ekstraksi gigi: serial kasus - Nurmaifah; Mohammad Gazali; Andi Tajrin (Makassar Dental Journal, 2022)
Background: Bleeding is a recognized complication, frequently encountered immediately following the removal of a tooth. This bleeding can be easily controlled in most cases, and almost completely stops within eight hours after the extraction. However, sometimes it may continue, resulting in a life‐threatening situation. Cases: Six cases of post-extraction bleeding due to local and systemic factors with different etiologies were presented, followed by a literature review to further discuss the diagnosis and management of bleeding. Conclusions: Bleeding after tooth extraction requires a careful history and evaluation in establish-ing a diagnosis with appropriate management to avoid more serious bleeding complications.